2021
DOI: 10.1016/j.clinthera.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulation Therapy for Venous Thromboembolism in Norway: Time Trends and Treatment Patterns

Abstract: Purpose: Data describing treatment patterns of patients with venous thromboembolism (VTE) patients in Scandinavia are scarce. This study sought to address this scarcity by describing demographic and clinical characteristics, trends in the use of oral anticoagulants (OACs), and treatment patterns in patients treated for VTE in Norway between 2013 and 2017.Methods: Using data from Norway's nationwide registries, a cohort study included patients newly (after 2008) treated OACs who were diagnosed with VTE between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…The temporal trends of initial anticoagulant therapy in the group without active cancer indicated decreases for warfarin but increases for NOACs, a trend that was consistent with that reported in several previous studies. 21 22 23 24 In particular, rivaroxaban was the most prescribed NOAC across all studies, likely because of the rapid market access and preference toward a once-daily dosing regimen. 25 Sizeable proportions of noncancer patients who initiated PAC were observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal trends of initial anticoagulant therapy in the group without active cancer indicated decreases for warfarin but increases for NOACs, a trend that was consistent with that reported in several previous studies. 21 22 23 24 In particular, rivaroxaban was the most prescribed NOAC across all studies, likely because of the rapid market access and preference toward a once-daily dosing regimen. 25 Sizeable proportions of noncancer patients who initiated PAC were observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is in line with several drug utilization studies. 14,15,27 Prescriptions on warfarin decreased by over 25% within the four-year period. Dabigatran and rivaroxaban accounted for approximately 60% of the total ED oral anticoagulant prescriptions in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Several studies have been conducted to investigate the prescription of anticoagulants in VTE patients to obtain an extensive understanding of this gap between medical recommendations and clinical practice. 14,15 However, little is known concerning the trend in anticoagulant prescription for ED patients with VTE. 12 The current study retrieved all available prescriptions of anticoagulants from the EDs of four major cities in China as representatives.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Anticoagulant treatment for subsequent VTEs was assumed to be either DOACs or phased anticoagulation (LMWH followed by warfarin); a 40:60 split was assumed based on registry data, [22] with higher use of DOACs explored in a scenario analysis given contemporaneous international data suggesting wider use with increasing familiarity. [23] The effectiveness of prophylactic LMWH was taken from a systematic review and network metaanalysis conducted by Wade et al, which reported the odds ratio (OR) for LMWH versus no LMWH (OR=0.26, 95% Confidence Interval [CI] 0.09 to 0.87) for the outcome of hospital acquired VTE in surgical patients. [24] Subsequent research published after completion of our work confirms this estimate of effectiveness; Marcucci et al report the OR for LMWH to range between 0.19 and 0.33 (depending on dose) for the outcome of symptomatic VTE compared to no active treatment, within a cohort of 45,445 patients undergoing non-cardiac surgery.…”
Section: Risk Assessment Modelsmentioning
confidence: 99%